Hepatocyte‐derived extracellular vesicles regulate liver regeneration through a negative feedback mechanism - Mina McGinn; Christopher Rabender; Ross Mikkelsen; Vasily Yakovlev (Journal of Extracellular Biology)
Abstract While significant progress has been made in understanding various aspects of liver regeneration, the molecular mechanisms responsible for the initiation and termination of cell proliferation in the liver following massive tissue loss or injury of liver remain unknown. As it was previously shown, the loss of liver mass affects putative hepatocyte‐specific mitogenic inhibitors in the blood. Although the presence of these putative inhibitors regulating precise liver regeneration has been described in numerous publications, they have never been identified. Extracellular vesicles (EVs) are nano‐sized, membrane‐limited structures secreted by cells into the extracellular space. Their proposed role is stable intercellular carriers of proteins and RNAs, predominantly micro‐RNA, from secreted to recipient cells. Upon uptake by the recipient cells, EVs can significantly modulate their biological functions. In the present study, using in vivo and in vitro models, we demonstrate that hepatocyte proliferation and liver regeneration are regulated by EVs secreted by hepatocytes into the bloodstream. This regulation occurs through a negative feedback mechanism, which explains the precise regeneration of liver tissue after massive damage. We also demonstrate that an essential component of this mechanism is RNA carried by hepatocyte‐derived EVs. Our findings open up a new and unexplored area of liver biology regarding the mechanisms involved in the precise regulation of liver regeneration after a massive tissue loss or injury. Further study of this mechanism will have a great influence on the development of new approaches to liver transplantation, various liver pathologies, and hepatic tumors.